GABAergic Contributions to the Pathophysiology of Depression and the Mechanism of Antidepressant Action - Sanacora, Gerard; Saricicek, Aybala (CNS & Neurological Disorders - Drug Targets, 2007)
Increasing evidence suggests that abnormalities in amino neurotransmission are associated with the neurobiology of depression. Preclinical studies demonstrate that GABA modulating agents are active in commonly used rodent behavioral models of antidepressant activity, and that chronic administration of antidepressant drugs induces marked changes in GABAergic function. In humans, depressed patients have lower plasma, CSF and brain GABA concentrations than non-depressed comparison subjects. The recent discovery that several anticonvulsant and GABA-mimetic agents possess mood stabilizing and antidepressant properties has further increased interest in these findings. This review outlines the existing literature investigating the possible involvement of GABA in the neurobiology of depression and briefly highlights how this information may afford new targets for antidepressant drug development.
Keywords: mood disorders